MSME Digitalization Strategy in Makassar City: Efforts to Increase Competitiveness in the Digital Economy Era - Elisabeth Ambalele; Andi Herman Tellu (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the national and regional economy, including in Makassar City. However, many MSME actors face obstacles in adopting digital technology due to limited literacy, inadequate access, and high costs. This condition hurts the competitiveness of products and services in the midst of global competition. This research aims to formulate a relevant and applicable MSME digitalization strategy to increase competitiveness in the digital economy era. A mixed-methods approach was employed, comprising a survey of 30 MSME actors, as well as in-depth interviews and Focus Group Discussions (FGDs) with local stakeholders. Data analysis was conducted descriptively and qualitatively using the Miles & Huberman approach, as well as a SWOT analysis, to identify the strengths, weaknesses, opportunities, and threats faced. The results of the study indicate that the digitization of MSMEs in Makassar is still in its early stages, with a predominance of social media use for marketing, but lagging in digital management and the adoption of financial applications. Key barriers include limited digital skills, transformation costs, and suboptimal ecosystem support. The recommended strategies include increasing digital literacy, collaboration with technology providers, and supporting local government policies. This research is expected to serve as the basis for formulating policies and strategic models for the digitalization of MSMEs, which can be replicated in other regions of Indonesia